Croatian version of Selection, optimization and compensation questionnaire, and its demographic correlates - Brković, Irma (2008)
Theoretical framework of SOC model (Baltes et al., 1997 ; 1999 ; 2002) is developed to gain a better understanding of the factors contributing to a successful development. It attempts to specify the self-regulation strategies people use to master their lives. The aim of research presented here was twofold: to develop Croatian version of SOC questionnaire and check its psychometric properties and to examine demographic correlates of SOC scores. The sample consisted of 335 adults (202 women and 133 men). The questionnaire consisted of 49 dichotomous items measuring 4 dimensions hypothesized by the model (Elective Selection, Loss-Based Selection, Optimization and Compensation). Analyses revealed that the subscales reached psychometric properties similar to those of the original version of the questionnaire (Cronbach alpha’ s ranging from 0, 50 to 0, 70) with low to moderate intercorrelations. Considering the length of the questionnaire suggestions for its shortening are discussed, showing that short versions keep good or gain improved psychometric properties. More educated participants, both women and men, showed higher results on Loss-based selection scale. Men reached higher scores than women on Elective selection. Age differences varied depending on subscale and gender. Correlations between spouses were found low but significant for Loss-based selection and Compensation subscales.
Projekt MZOS
ENG